The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4317/jced.56022
|View full text |Cite
|
Sign up to set email alerts
|

The Micro-Shear bond strength of different cements to commercially pure titanium

Abstract: BackgroundThe most appropriate luting agent for attaching the prefabricated Ti-based insert of hybrid abutments to its ceramic component has not yet been determined. This study was done aimed at examining the micro-shear bond strength (μSBS) of different cements to commercially pure titanium (Cp Ti).Material and MethodsA total of 100 milled cubes of Cp Ti was airborne-particle abraded using 250 μm aluminum oxide particles. Specimens were then divided into 5 groups (n=20) according to the type of resin cement u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…According to the results of the present study, adhesive fracture was the predominant failure mode with respect to the fact that resin cement monomers contain many carbon-carbon double bond units, which produce a high degree of matrix cross-linking and, consequently, high mechanical properties [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results of the present study, adhesive fracture was the predominant failure mode with respect to the fact that resin cement monomers contain many carbon-carbon double bond units, which produce a high degree of matrix cross-linking and, consequently, high mechanical properties [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study conducted by Nakhaei et al [ 14 ], which examined the SBS of different cements to cp-Ti, demonstrated Panavia F.2 as the best choice for bonding to cp-Ti. In another study, Nakhaei et al [ 26 ] investigated the SBS of different bonding protocols to commercially pure titanium (cp-Ti) through the use of two universal adhesives, including Scotchbond Universal (SU; 3M ESPE, St. Paul, MN, USA) and G-Premio Bond (GC Corporation, Tokyo, Japan) and Alloy Primer (AP; Kuraray).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Various studies evaluating the bond strength of resin-based luting agents to titanium are available in the literature. 16 20 29 30 31 32 33 However, different results emerged even in the studies using similar luting agent types. These differences could be due to the primers used, specimen differences in study design, or compositional differences in luting agents, including different ratios of monomers and chemical/light catalysts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alloy surfaces should be decontaminated with ultrasonic cleansing [ 52 ]. However, Al 2 O 3 remained embedded on the titanium surfaces, and these encrusted particles establish chemical affinity between functional monomers of resin materials and themselves, increasing the resin cement's binding strength [ 53 ].…”
Section: Discussionmentioning
confidence: 99%